Risks of phase I research with healthy participants: A systematic review. (April 2016) - Johnson, Rebecca A; Rid, Annette; Emanuel, Ezekiel; Wendler, David
Background/aims: Tragedies suggest that phase I trials in healthy participants may be highly risky. This possibility raises concern that phase I trials may exploit healthy participants to develop new therapies, making the translation of scientific discoveries ethically worrisome. Yet, few systematic data evaluate this concern. This article systematically reviews the risks of published phase I trials in healthy participants and evaluates trial features associated with increased risks. Methods: Data on adverse events and trial characteristics were extracted from all phase I trials published in PubMed, Embase, Cochrane, Scopus, and PsycINFO (1 January 2008–1 October 2012). Inclusion criteria were phase I studies that enrolled healthy participants of any age, provided quantitative adverse event data, and documented the number of participants enrolled. Exclusion criteria included (1) adverse event data not in English, (2) a "challenge" study in which participants were administered a pathogen, and (3) no quantitative information about serious adverse events. Data on the incidence of adverse events, duration of adverse event monitoring, trial agent tested, participant demographics, and trial location were extracted. Results: In 475 trials enrolling 27, 185 participants, there was a median of zero serious adverse events (interquartile range = 0–0) and a median of zero severe adverse events (interquartile range = 0–0) per 1000 treatment group participants/day of monitoring. The rate of mild and moderate adverse events was a median of 1147.19 per 1000 participants (interquartile range = 651.52–1730.9) and 46.07 per 1000 participants/adverse event monitoring day (interquartile range = 17.80–77.19). Conclusion: We conclude that phase I trials do cause mild and moderate harms but pose low risks of severe harm. To ensure that this conclusion also applies to unpublished trials, it is important to increase trial transparency.